Know Thy Neighbor: Industry Clusters, Information Spillovers, and Market Efficiency - Engelberg, Joseph; Ozoguz, Arzu; Wang, Sean (Journal of Financial and Quantitative Analysis, 2018)
Firms in industry clusters have market prices that are more efficient than firms outside clusters. To establish causality, we analyze exogenous firm relocations and find that firms that relocate into industry clusters have higher levels of industry information in their prices. We argue that geographical proximity allows for information spillovers, reducing marginal cost to information producers. Our evidence supports this view: Analysts are more likely to cover stocks inside industry clusters, and when institutional investors have a large position in one stock in the industry cluster, they are more likely to hold other stocks in the same industry cluster.